How ‘Transitional Justice’ Colonized South Africa’s TRC - Ronald Suresh Roberts (Modern Languages Open, 2020)
Commentators have wrongly assumed that the operations and outcomes of South Africa’s Truth and Reconciliation Commission (TRC) reflected the intentions of the African National Congress (ANC) government that instigated it. In line with its agenda of substantive social history, the ANC intended to establish a new Gramscian ‘common sense’ of anti-colonialism and self-determination to drive anti-apartheid transformation. As part of its additional aim for an institutional intervention, the ANC sought to renovate the inherited technology of the colonial commission of inquiry itself. As the paper shows, these aims were overturned through the superimposition of ‘transitional justice’ within the workings of the TRC and the TRC’s ‘Final Report’. The continuing implications of this abduction are addressed in closing.